PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA GURU DIMODERASI SUPERVISI (Studi Kasus pada Guru-guru PNS SD di UPT Dinas pendidikan Kecamatan Gunem Kabupaten Rembang) (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study was conducted to examine the effect of the variables of teacher motivation and discipline to the performance of civil service teachers in the District Education Office UPT Gunem with supervision as a moderating variable. The population in this study was the civil servant teachers in elementary schools - District of Gunem , as many as 116 people Rembang . Data were collected using questionnaires and the returned and processed as many as 114 . Test instruments used are validity and reliability . While ui model used is the coefficient of determination and test " F " . Test this hypothesis using regression analysis. The results showed motivation and discipline of work does not affect the performance of teachers , while supervising positive and significant effect on performance . While the results of multiple regression testing moderation model suggests that supervision is not able to moderate the effects of motivation on teacher performance , the effect of labor discipline on teacher performance . Keywords : Motivation , Discipline Work , Supervision , Performance